Role and Importance of Technological Credits in Financing of Innovative Investments by Small and Medium-sized Enterprises in Poland and Lesser Poland - Joanna Duda (Managerial Economics)
As globalisation and internationalisation proceed, innovativeness of small and medium-sized enterprises (SME) has become a key element to building of competitive advantage in the market. Polish SMEs are commonly regarded as not very innovative and encounter a range of barriers to access to external capital, in particular, bank crediting. Therefore, this paper analyses investment spending and sources of financing for innovative activities in this group of enterprises on the basis of literature and empirical studies. An attempt is also undertaken at assessing the potential for obtaining and using of technological credits in order to finance innovative activities.